Aggregate Production Functions Revisited: The Mobility of Capital and the Rigidity of Thought - Fisher, Franklin M. (Review of Economic Studies, 1982)
Past work on aggregation of production functions has focused on aggregation over firms where technology is embodied in fixed capital. This paper shows that much of the stringency of the necessary conditions for aggregation resides in the nature of aggregation over firms and not in the immobility of capital. Roughly, when capital is mobile, aggregation is permitted for any group of factors under the union of the conditions which otherwise applied to aggregation of fixed or aggregation of movable factors, respectively. No truly new conditions appear. The results are also interpreted in terms of output aggregation.